Nanoscale Titanium Oxide Memristive Structures for Neuromorphic Applications: Atomic Force Anodization Techniques, Modeling, Chemical Composition, and Resistive Switching Properties - Vadim I. Avilov; Roman V. Tominov; Zakhar E. Vakulov; Daniel J. Rodriguez; Nikita V. Polupanov; Vladimir A. Smirnov (Nanomaterials)
This paper presents the results of a study on the formation of nanostructures of electrochemical titanium oxide for neuromorphic applications. Three anodization synthesis techniques were considered to allow the formation of structures with different sizes and productivity: nanodot, lateral, and imprint. The mathematical model allowed us to calculate the processes of oxygen ion transfer to the reaction zone; the growth of the nanostructure due to the oxidation of the titanium film; and the formation of TiO, Ti2O3, and TiO2 oxides in the volume of the growing nanostructure and the redistribution of oxygen vacancies and conduction channel. Modeling of the nanodot structure synthesis process showed that at the initial stages of growth, a conductivity channel was formed, connecting the top and bottom of the nanostructure, which became thinner over time; at approximately 640 ms, this channel broke into upper and lower nuclei, after which the upper part disappeared. Modeling of the lateral nanostructure synthesis process showed that at the initial stages of growth, a conductivity channel was also formed, which quickly disappeared and left a nucleus that moved after the moving AFM tip. The simulation of the imprint nanostructure synthesis process showed the formation of two conductivity channels at a distance corresponding to the dimensions of the template tip. After about 460 ms, both channels broke, leaving behind embryos. The nanodot, lateral, and imprint nanostructure XPS spectra confirmed the theoretical calculations presented earlier: in the near-surface layers, the TiO2 oxide was observed, with the subsequent titanium oxide nanostructure surface etching proportion of TiO2 decreasing, and proportions of Ti2O3 and TiO oxides increasing. All nanodot, lateral, and imprint nanostructures showed reproducible resistive switching over 1000 switching cycles and holding their state for 10,000 s at read operation.